2006
DOI: 10.1111/j.1751-0813.2006.tb13115.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of bacteria from feline and canine urinary tract infections to doxycycline and tetracycline concentrations attained in urine four hours after oral dosage

Abstract: Objectives To measure urinary concentrations of doxycycline in cats and dogs and tetracycline in dogs 4 h after conventional oral dosing and determine whether these antibiotics were present in sufficient concentrations to be effective against common feline and canine urinary tract pathogens as assessed in vitro by Epsilometer and disc diffusion antimicrobial susceptibility methods. Design A prospective study involving oral administration to clinically normal cats and dogs of doxycycline or tetracycline (dogs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The comparative results of that 1994 study may infer that a greater number of resistant E. coli isolates are collected from North American than Australian dogs. Similar observations have been noted with other antibacterials, such as fluoroquinolones and tetracyclines, against Australian canine and feline E. coli isolates . Likewise, a low number of ticarcillin‐susceptible E. coli isolates (45%) from canine urine samples was reported from Portugal; however, our study had a susceptibility of 75%.…”
Section: Discussionsupporting
confidence: 89%
“…The comparative results of that 1994 study may infer that a greater number of resistant E. coli isolates are collected from North American than Australian dogs. Similar observations have been noted with other antibacterials, such as fluoroquinolones and tetracyclines, against Australian canine and feline E. coli isolates . Likewise, a low number of ticarcillin‐susceptible E. coli isolates (45%) from canine urine samples was reported from Portugal; however, our study had a susceptibility of 75%.…”
Section: Discussionsupporting
confidence: 89%
“…Among the 6 antibiotics tested, resistance was most frequent to tetracycline. However, a recent study [11], showed that concentrations of doxycycline attained in the urine of dogs were sufficient to inhibit the growth of a significant number (35/45) of urinary tract pathogens. In any case, the present study showed that enrofloxacin had the least resistance; more than 80% of all isolates being susceptible.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this study, a few studies have been published to describe PK properties of doxycycline in dogs (10)(11)(12)(13)(14)(15)(16)(17). One additional study was identified (30), but analysis of the plasma concentrations from that study produced values far out of the range of those listed in Table 1; therefore, those data were not incorporated into this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics of doxycycline in dogs have been assessed in previously published studies on the oral administration of doxycycline (10,11), the findings of a conference presentation (A. Dominguez, B. Kukanich, and K. Kukanich, presented at the American Academy of Veterinary Pharmacology and Therapeutics 18th Biennial Symposium, Potomac, MD, 20 to 23 May 2013), and one unpublished study performed by one of the veterinary drug sponsors (S. T. B. Rogar, unpublished data). Other studies of nonoral administration in dogs have been published for comparison with studies of oral administration and determination of protein binding (12)(13)(14)(15)(16)(17). The oral administration studies used for this analysis used a validated assay and uniform methods.…”
Section: Bacterial Isolatesmentioning
confidence: 99%